On the norms of charitable giving in Islam: A field experiment - Fatima Lambarraa; Gerhard Riener (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
Charitable giving is one of the major obligations Islam and a strong Muslim norm endorses giving to the needy, but discourages public displays of giving. This norm is puzzling in light of previous evidence, suggesting that making donations public often increases giving. We report the results two field experiments with 534 and 186 participants at Moroccan educational institutions (among them two religious schools) to assess the effects this moral prescription on actual giving levels in anonymous and public settings. Subjects who participated in a paid study were given the option to donate from their payment to a local orphanage, under treatments that varied the publicity of the donation and the salience of Islamic values. In the salient Islamic treatment, anonymity of donations significantly increased donation incidence from 59% to 77% percent as well as average donations for religious subjects from 8.90 to 13.00 Dh. This findings stand in stark contrast to most previous findings in the charitable giving literature and suggest to rethink fundraising strategies in Muslim populations.
Keywords: H40; C93; D01; Z12; 330; Charitable giving; Islam; Social pressure; Priming; Religion; Norms; Field experiment